Crystallization manipulation and morphology evolution for highly efficient perovskite solar cell fabrication via hydration water induced intermediate phase formation under heat assisted spin-coating. Issue 7 (25th January 2018) - Zhou, Xianyong; Zhang, Yong; Kong, Weiguang; Hu, Manman; Zhang, Luozheng; Liu, Chang; Li, Xiangnan; Pan, Chunyue; Yu, Guipeng; Cheng, Chun; Xu, Baomin
Abstract : A delicate control of crystallization and the morphology of perovskite absorbers is critical to obtain high performance hybrid perovskite solar cells (PSCs). Abstract : A delicate control of crystallization and morphology of perovskite absorbers is critical to obtain high performance hybrid perovskite solar cells (PSCs). Here, we have developed a novel crystallization strategy which involves hydration water induced intermediate phase formation under heat assisted spin-coating processing (HASP) to manipulate the morphology and grain size of perovskite films, and thus it can avoid the use of toxic and volatile antisolvents used in conventional one-step solution processes to make PSCs. During HASP, impressive morphological evolution of films occurs with the formation of CH3 NH3 PbI3 · x H2 O perovskite intermediate phases. With ingenious control of the crystallization kinetics, highly crystalline perovskite films with fewer defect states and high carrier lifetimes are obtained. The corresponding PSCs exhibit a power conversion efficiency (PCE) of 19.12% with a stabilized power output efficiency of 18.89% at the maximum power point, which is a 70% enhancement compared to that of conventional one-step process based PSCs. Furthermore, the PSC fabricated by the HASP method achieved a PCE of 15.47% with an active area of 1.2 cm 2 . Moreover, the flexible PSCs fabricated by the HASP method achieved a record efficiency of 14.87% with negligible hysteresis for PEDOT:PSS-based flexible inverted PSCs. Our work opens up a new avenue for morphology and crystallization control through hydration water induced intermediate phase formation under HASP, which paves the way toward further enhancing the device performance of perovskite solar cells.